Gambaran Kesepian pada Remaja Pelaku Self Harm - Lubis, Irma Rosalinda; Yudhaningrum, Lupi (Journal of Research and Measurement in Psychology: JPPP, 2020)
Loneliness is an unpleasant situation experienced by someone because they have a lack of emotional and social relationships with others. Everyone can feel lonely, regardless of age, gender, or socioeconomic status. Society has the idea that people with old or advanced age experience loneliness more often. However, it turns out, people with adolescence experience loneliness more often than people with old or advanced age. This research was conducted with the aim to see a description of loneliness in adolescents who do self harm. The limitation of this study is that among the many problems faced by adolescents, researchers will limit the problems to self-harm behavior and see how the description of loneliness in adolescents who do it. This research was conducted using a qualitative approach to the type of case study. The data analyzed were the results of interviews and observations with two adolscent participants. The results showed that of the three lonely themes put forward by Weiss, namely family loneliness, romantic loneliness, and social loneliness, both adolescent participants who experienced self harm had feelings of loneliness in these three themes, and family loneliness had the greatest role in adolescents. . Keywords: Loneliness, Adolescent, Self Harm.